A liberdade sexual administrada - Silva, Pedro Fernando da (2007)
This objectives research are to investigate the correlations between attitudes concerning to the sexual liberation, the desexualization and the conformism; and to elucidate some contradictions of the psychosocial structure of the administrated sexual liberty. The general hypothesis supposes that this regressive phenomenon is a contradictory expression of the freedom desire made under the not-free world determinations. The administrated sexual liberty incidence, such as the correlations between the implicated attitudes in her structure, was examined by empirical investigation and theoretical speculation. For to realize this purpose, three scales type Likert was elaborated: conformism scale (C), sexual liberation scale (LS), and desexualization scale (D). These scales were applied in 135 university students from Great São Paulo, and the final sample has 77 individuals. The correspondent dates were submitted to statistical tests, permitting to verify the scales precision and to obtain correlations between the measured attitudes. The instruments precision was verified by Alpha of the Cronbach, who was satisfactory in the three cases, with the following coefficients: 0,89 in the scale C, 0,77 in the scale LS, and 0,76 in the scale D. The found results confirm the hypothesis, and permit to demonstrate that there is a significant correlation between the characterized attitudes to the desexualization and the inclination to the conformism. Although the favorable attitudes to the liberation sexual, as much as the attitudes characterized to the desexualization, were related with contemporary forms and patterns of the sexual behavior, the results do not indicate significant correlation between them. Also there not is significant correlation between the conformist attitudes and the adhesion to the sexual liberation. Among the mediation of the administrated sexual liberty studied in this research, the desexualization is the form of the sexual liberty regression more directly implicated in the adjustment of the individuals to the conditions of the existence imposed to them nowadays